Tipos de suma de cuadrados en el análisis de la varianza (2007)
ABSTRACT: The sum of squares is used in order to carry out a decomposition of the entire variability attributable to a response variable Y in the different components or controlled or manipulated factors by the an investigator X, and the addition of the experimental error that constitutes the source of variation that agglutinates all the not controlled components inside the model of experimental classification.